Characterization of Manganese/Molybdenum Mixed Oxides - Afaf Zahran (Adsorption Science & Technology)
Samples of manganese oxide (Mn 3 O 4 ) were prepared from MnCl 2 solutions of different concentrations (0.025, 0.05, 0.10 and 0.50 N) via precipitation using NH 4 OH aqueous solution. Although similar in chemical structure, the samples obtained showed different textures corresponding to the calcination temperature employed up to 900°C. Loading these samples with different amounts of Mo followed by calcination at 900°C led to the formation of MnMoO 4 samples displaying variable modes of dispersion on their surfaces. The variable distribution of surface hydroxy groups on the samples due to their different textures caused changes in the manner in which the Mo species and the manganese oxide surface interacted, and consequently the final state of the samples obtained after calcination at 900°C differed. Stabilization of the initially formed hausmannite was only detected for Mo-loaded samples prepared from a 0.025 N solution and calcined at 900°C. This behaviour was not observed in the case of the other three samples studied. This stabilization is attributed to localized growth of MnMoO 4 that caused the under-layer regions to be subjected to different environmental conditions during the calcination/cooling processes.